2010
DOI: 10.1002/asi.21442
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness in mHealth information services: An assessment of a hierarchical model with mediating and moderating effects using partial least squares (PLS)

Abstract: The aim of this research is to advance both the theoretical conceptualization and the empirical validation of trustworthiness in mHealth (mobile health) information services research. Conceptually, it extends this line of research by reframing trustworthiness as a hierarchical, reflective construct, incorporating ability, benevolence, integrity, and predictability. Empirically, it confirms that partial least squares path modeling can be used to estimate the parameters of a hierarchical, reflective model with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(238 citation statements)
references
References 114 publications
7
191
1
Order By: Relevance
“…Trust is defined as an act of a trustor (Corritore, Kracher, & Wiedenbeck, 2003), however, trustworthiness is acknowledged as the characteristics of trustees that are worthy to trust (Rusman, Van Bruggen, & Koper, 2007). According to Serva, Benamati, and Fuller (2005), trustworthiness leads to trust and both of these are not similar but are linked with each other (Akter, D'Ambra, & Ray, 2011). In this study, trustworthiness is played a role as mediator.…”
Section: Trustworthinessmentioning
confidence: 60%
See 1 more Smart Citation
“…Trust is defined as an act of a trustor (Corritore, Kracher, & Wiedenbeck, 2003), however, trustworthiness is acknowledged as the characteristics of trustees that are worthy to trust (Rusman, Van Bruggen, & Koper, 2007). According to Serva, Benamati, and Fuller (2005), trustworthiness leads to trust and both of these are not similar but are linked with each other (Akter, D'Ambra, & Ray, 2011). In this study, trustworthiness is played a role as mediator.…”
Section: Trustworthinessmentioning
confidence: 60%
“…In this study, GOF value was 0.61 (R 2 = 0.747, average AVE = 0.661 for e-loyalty) and 0.72 (R 2 = 0.808, average AVE = 0.796 for trustworthiness). Both of GOF value exceeded the largest cut-off value (0.36) and it was indicated that the proposed model of this study had better explaining power than that based on the recommended value of GOF small = 0.1, GOF medium = 0.25, and GOF large = 0.36 (Akter et al, 2011). …”
Section: Assessment Of the Structural Modelmentioning
confidence: 62%
“…Required assessments for the measurement and structural model were carried out on accordance to [4], [5] suggestions. [6,8]. This means that the model has achieved the required validity process.…”
Section: Model's Constructionmentioning
confidence: 95%
“…[4] stated that the most commonly used measure to evaluate the structural model is the coefficient of determination (R² value). The indicator used to describe the explanatory power is the model's coefficient of determination which is (R²) value [1,8,6]. According to [11], a model can be assessed as substantial if (R²) equal or more than 0.26, moderate if (R²) equal or more than 0.13 and weak if (R²) equal or less than 0.02.…”
Section: Explanatory Powermentioning
confidence: 99%
“…Mobile health (mHealth) is the provision of health services and information via mobile devices, such as smartphones, tablet and laptop computers, and personal digital assistants (PDAs) (Akter et al 2011). mHealth can enable healthcare that is "more accessible, affordable and available" (Akter et al 2013 p. 181), given that the majority of people throughout the world (more than 5.5 billion people) own a mobile phone (Akter et al 2013) and their tendency to keep them close at hand at all times (Klasnja and Pratt 2012).…”
Section: Introductionmentioning
confidence: 99%